Fractionation of the geochemical twins Zr–Hf and Nb–Ta during scavenging from seawater by hydrogenetic ferromanganese crusts - Schmidt, Katja; Bau, Michael; Hein, James R.; Koschinsky, Andrea (Geochimica et cosmochimica acta, 2014)
In contrast to igneous systems, the geochemical twins Zr and Hf are decoupled from each other in seawater, and specific Zr/Hf ratios appear to be characteristic of individual marine water masses. Hydrogenetic marine ferromanganese (Fe–Mn) crusts which accumulate trace metals from seawater may be an archive of Zr/Hf ratios that reveal changes in oceanic paleocirculation over millions of years. To verify whether Fe–Mn crusts truly reflect the Zr–Hf distribution in seawater, we studied these particle-reactive elements together with Nb and Ta (another geochemical twin pair) in bulk Fe–Mn crusts and their surface layers from different locations in the Atlantic and Pacific oceans. Zirconium (400–1000mgkg−1), Hf (5–18mgkg−1), Nb (42–83mgkg−1) and Ta (0.5–1.5mgkg−1) are significantly enriched in Fe–Mn crusts relative to the average continental crust, and their Zr/Hf and Nb/Ta ratios are super-chondritic (57–87 and 35–96, respectively), whereas the continental crust shows ratios close to those of chondrites. We emphasize that neither bulk Fe–Mn crusts nor their surface layers match the Zr/Hf or Nb/Ta ratios of modern deep seawater, but are lower and higher, respectively. The presence of aluminosilicate detritus cannot explain the different Zr/Hf ratios of crusts and ambient seawater, as potential detritus has much lower Zr and Hf concentrations. Consequently, these geochemical twins must be fractionated during their removal from seawater and their incorporation into Fe–Mn (oxyhydr)oxides. Hafnium is preferentially scavenged as shown by Zr/Hf ratios of crust surface layers (75–100) that are always below those of modern deep seawater (150–300). The decoupled behavior of geochemical twins during sorption, which is also observed for Nb–Ta, can be related to differences in the electron structures of these elements. Iron-normalized concentrations of Zr, Hf, Nb, and Ta increase with increasing size of the positive Ce anomaly (known to increase with decreasing growth rate), which is accompanied by decreasing Zr/Hf and Nb/Ta ratios. Concentrations and ratios of Zr–Hf and Nb–Ta in the crusts are controlled by the Fe/Mn ratio, the growth rate of a crust, and by the composition of ambient seawater. On a basin-wide scale, the variation of Zr/Hf ratios in Fe–Mn crusts, although different from those of ambient seawater, generally reflects the variation of the regional seawater. Compared to Fe–Mn crusts from the Central Pacific, crusts from the NE Atlantic display lower Zr/Hf and Nb/Ta ratios. This likely reflects the lower Zr/Hf ratios in Atlantic deep water compared to Pacific deep water. Although the Zr/Hf ratio of Fe–Mn crusts broadly reflects major changes in seawater circulation, the Zr/Hf signatures of individual Fe–Mn crust layers cannot be used as a paleoceanographic proxy because they are continuously modified by ongoing sorption. Sorption of Zr and Hf onto Fe and/or Mn (oxyhydr)oxides that occur either as discrete particles or as particle coatings, appear to be an efficient way to fractionate Zr and Hf and may significantly contribute to the continuous fractionation of dissolved Zr and Hf observed in seawater.